Réponses

Meilleure réponse !
2014-09-06T15:41:14+02:00
  • Utilisateur Brainly
2014-09-06T15:42:43+02:00
(x + 1)(- 5x - 2) = 0

x + 1 = 0 ou - 5x - 2 = 0
x = - 1 ou 5x = - 2
x = - 1 ou x = - 2/5

S {- 1 ; - 2/5}
                                                                                                                                 
x                      - ∞                         - 1                              - 2/5                        +∞      
(x + 1)                        -                   0                  +                                +
(- 5x - 2)                    +                                       +               0               -                     
(x + 1)(- 5x - 2)           -                  0                   +              0               -